+0  
 
0
50
1
avatar

if (x^2 + y^2)/(xy) = 8, then find (x^6 + y^6)/(x^3*y^3).

 Dec 3, 2019
 #1
avatar+106539 
+1

( x^2 + y^2) / (xy)  =  8      (1)

 

(x^6 + y^6) / ( x^3y^3)   =   ( x^2 +y^2) ( x^4 - x^2y^2 + y^4) / (x^3y^3)   (2)

 

Rearrange (1)  as    (x^2 + y^2) = 8(xy)   sub into  (2)

 

8 ( xy)  ( x^4 - x^2y^2  + y^4) / ( x^3y^3)  =   8 ( x^4 - x^2y^2 + y^4) / (x^2y^2)      (3)

 

And  

 

(x^2 + y^2)  = 8xy       square both sides

 

x^4 + 2x^2y^2 + y^4  =  64x^2y^2

 

2x^2y^2  =   64x^2y^2 - x^4 - y^4        add  -3x^2y^2 to both sides

 

-x^2y^2  =  61x^2y^2  - x^4 - y^4     sub this into  (3)   and we have that  

 

8 ( x^4 + (61x^2y^2 - x^4 - y^4) + y^4)  / ( x^2y^2)  

 

8  ( 61x^2 y^2)  / (x^2y^2)  =

 

8 * 61  =

 

488

 

 

cool  cool  cool

 Dec 3, 2019
edited by CPhill  Dec 3, 2019

30 Online Users

avatar
avatar
avatar